Pendampingan Kelompok Tani Pade Angen dalam Memanfaatkan Tanaman Pekarangan Menjadi Olahan Produk di Desa Peresak Kabupaten Lombok Barat - Rosalina Edy Swandayani; Meilinda Pahriana Sulastri; Mimi Cahayani (Jurnal Pengabdian UNDIKMA, 2022)
The study aims to educate the community to optimize the yard and turn the results of the yard plants into marketable products. The methods of implementing this service were assistance and training in making processed yard products in the form of packaged herbal drink products. The service partners were members of the Pade Angen Farmers Group. Evaluation of activities was carried out by giving participants pre-test and post-test to measure service activities' success. The result showed that using yardland could increase public understanding to optimize yardland and produce processed products marketed as packaged herbal drink products to help increase people's income and welfare during the Covid-19 pandemic.